Development and application of a highly sensitive quadruple droplet digital PCR method for simultaneous quantification of sulfonamide resistance genes - Yin, Xirong; Nie, Jiayuan; Tian, Huifang; Duan, Lihong; Wu, Lixia; Xu, Xiangdong; Guo, Yumei; Wang, Ke (Frontiers in Microbiology, 2025)
Sulfonamide resistance genes (sul genes) have a high detection rate and strong transmissibility. Therefore, there is an urgent need to develop more efficient detection methods to enhance the monitoring of sul genes. Current analytical methods are insufficient for the simultaneous and accurate quantification of all sulfonamides resistance genes. To overcome this limitation, a quadruple method was established by integrating droplet digital PCR (ddPCR) with the ratio-based probe-mixing strategy, achieving sensitive detection of sul1, sul2, sul3, and sul4 genes in diverse matrices. Correspondingly, the primers and probes of sul genes were meticulously designed and rigorously validated, and the critical parameters for ddPCR such as annealing temperature, concentrations of primers and probes were systematically optimized. As a results, the quadruple ddPCR method demonstrates excellent sensitivity with limits of detection (LOD) ranging from 3.98 to 6.16 copies/reaction, and good repeatability (coefficient of variation <25%), adequately meeting the requirement for accurate sul genes quantification. Furthermore, this new method was applied across 115 diverse samples, including human feces, animal-derived foods, sewage and surface water, achieving positive rates of 100% for sul1, 99.13% for sul2, 93.91% for sul3, and 68.70% for sul4, with sul genes concentration ranging from non-detection to 2.14 × 109 copies/g. In summary, the developed quadruple ddPCR method has potential to serve as an efficient and sensitive tool for monitoring sul genes.